Palatal mucormycosis in an immuno-competent infant following dengue haemorrhagic fever - Pathiraja, H.; Munasinghe, R.; Gunapala, R.; Fernando, J.; Gunaratne, S.; Pemasiri, C.; Jayasekara, P. (Sri Lanka College of Paediatricians, 2025)
No abstract available
Indexed in SLJOL.
Keywords: Mucormycosis; Necrosis; Hard palate; Liposomal amphotericin B